HANDLING CUSTOMER COMPLAINTS IN THE INDIGENOUS FOOD VENDING INDUSTRY - Azila-Gbettor, Edem Maxwell; Kwodjo Avorga, Simon Mesa; Atatsi, Eli Ayawo (European Scientific Journal, ESJ, 2014)
Format of customer complaint management process within formal organization has received considerable attention in the literature at the expense of informal sectors of most countries. Drawing on the work of Hansen et al. (2009), this paper examines operational complaint management procedure in the indigenous food vending industry in Ghana and customers complaint reaction. The paper presents result from quantitative research involving one thousand two hundred and ten (1,210) customers selected using convenience sampling technique, who visited ten (10) main traditional food vending restaurants within the Ho Township. The study conclusively shows consumers adopt passive and voiced attitude in complaint reaction. Furthermore, whiles vendors attempt in managing customer complaint in practice, however, in principle compensating customers is completely absent. We recommend participatory approach in determining what is fair and reasonable in determining customer compensation.